Book Review: Jing, T. (2022). The Origins and Continuity of Chinese Sociology. Springer, Singapore, pp. XV+502. - Gotsis, Georgios (Neusis, 2025)
This book systematically examines the origins and historical beginnings of social thought in China, indicating key milestones in a broader evolutionary intellectual path.